Broken rotor bar detection of three phase induction motor using frequency response analysis - Khan, Rizwanullah; Mohd Yousof, Mohd Fairouz; Rahman, Rahisham Abd; Azis, Norhafiz; Al-Ameri, Salem; Ali, Asjad (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Three phase induction motors (TPIMs) are broadly utilized for various applications in the industry, but they are prone to different faults that can affect their performance and reliability. One common fault is a broken rotor bar, which leads to vibration, noise, and reduced efficiency. Therefore, detecting and identifying this fault early is important to avoid further damage and reduce maintenance costs. This paper proposes a novel method using frequency response analysis (FRA) to diagnose broken rotor bars in a TPIM. The response of normal motor is measured to obtain the baseline. Subsequently, the rotor was inflected with physical damage to represent a broken rotor bar. By comparing normal and faulty rotors, the measurement shows that frequency response analysis is sensitive toward various fault severity based on the number of broken rotor bars.